Integrative effect of citrate on Cr(Ⅵ) and total Cr removal using a sulfate-reducing bacteria consortium. (September 2021) - Gu, Wenzhi; Zheng, Decong; Li, Daping; Wei, Cuicui; Wang, Xu; Yang, Qingzhuoma; Tian, Chang; Cui, Mengyao
Abstract: In controlling toxic Cr(Ⅵ) pollution, the sulfate-reducing bacteria (SRB) method—a bioresource technology—is considered more sustainable and stable than synthetic technologies; however, its mechanisms of metal removal are unclear. This study investigated the mechanism of the use of citrate as a carbon source in an SRB bioreactor for Cr(Ⅵ) removal by disassemble or simulation approach. We show that citrate can mask toxicity, whereby the IC50 value (inhibitory concentration affecting 50% of the test population) of citrate was higher than that of lactate, and that citrate can also protect water systems from oxidation. The anti-oxidation rate of citrate ranged from 76.00% to 90.92%; whereas for citrate‒Cr(Ⅲ), the oxidation rate was only 0.185%–0.587%. Citrate can up-regulate microbial genes and functions, causing acetate and sulfide (NaFeS2 ) accumulation. Acetate addition promoted Cr adsorption by sulfide (mainly NaFeS2 ) and promoted sulfide sedimentation. Moreover, in addition to Cr(Ⅵ) reduction and Cr(Ⅲ)‒sulfide generation, the addition of sulfide promoted sedimentation; the correlation coefficient between the sedimentation coefficient and the sulfur content was r = −0.88877 at p < 0.01. Therefore, citrate had a systemic radiative effect on every aspect of the SRB‒citrate system model for Cr(Ⅵ) removal. In addition to the reduction in the former simple model, an integrative effect (including adsorption, sedimentation, and metabolism) was combined with NaFeS2 for Cr removal, which was regulated by the SRB‒citrate system. Exploration and understanding of these mechanisms promote SRB‒citrate methods to be wider implications in practice. Graphical abstract: Image 1 Highlights: The role of citrate in a sulfate-reducing bacteria model was investigated. Citrate systematically enhanced hexavalent chromium removal from water. Optimal conditions for the bacterial consortium were achieved with citrate. Adsorption and sedimentation were related to NaFeS2 to remove chromium.